2021
DOI: 10.3389/fcvm.2021.641272
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phenotypes Induced by Different Degrees of Transverse Aortic Constriction in C57BL/6N Mice

Abstract: The transverse aortic constriction (TAC) model surgery is a widely used disease model to study pressure overload–induced cardiac hypertrophy and heart failure in mice. The severity of adverse cardiac remodeling of the TAC model is largely dependent on the degree of constriction around the aorta, and the phenotypes of TAC are also different in different mouse strains. Few studies focus on directly comparing phenotypes of the TAC model with different degrees of constriction around the aorta, and no study compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Use of 27 gauge (27G) needles result in severe cardiac impairment and HFrEF in larger mice. 77 However, there is evidence that suture-based TAC using the same 27G spacer, but various suture materials (silk versus monofil) for constriction resulted in a relative high LV mass variation and changes in LVEF. This might be due to different self-elastic quality of the sutures.…”
Section: Small Animal Models Of Pressure Overloadmentioning
confidence: 99%
“…Use of 27 gauge (27G) needles result in severe cardiac impairment and HFrEF in larger mice. 77 However, there is evidence that suture-based TAC using the same 27G spacer, but various suture materials (silk versus monofil) for constriction resulted in a relative high LV mass variation and changes in LVEF. This might be due to different self-elastic quality of the sutures.…”
Section: Small Animal Models Of Pressure Overloadmentioning
confidence: 99%
“…TAC-treated mice develop cardiac hypertrophy, cardiac fibrosis, inflammation, and eventually cardiac dilation and HF. The progression of this adverse cardiac remodeling induced by TAC is associated with the duration of aortic constriction ( 9 , 13 ). However, very few studies observed a time-series cardiac remodeling phenotype induced by TAC ( 11 , 20 , 21 ), especially in C57BL/6 J mice applied with a 25-gauge needle.…”
Section: Resultsmentioning
confidence: 99%
“…The constriction degree of the aorta arch is the most important factor affecting the phenotypes of TAC-induced cardiac remodeling. The constriction diameter of the needles used for TAC varied from 17-gauge to 30-gauge, but a 27-gauge needle has been the most common needle size (>70%) for constriction in TAC study ( 9 , 10 , 13 , 16 , 28 ). Several studies have compared the resulting phenotypes to different needles, including 25-gauge, 26-gauge, and 27-gauge needles ( 9 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…TAC can induce left ventricle systolic dysfunction and cardiac remodeling in mice ( 23 ). The results of previous experiments on the conditional increase/decrease in HIF-1α expression observed in mice following TAC surgery appear to be contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…The TAC and CIH exposure protocols were approved by the Animal Experiment Ethics Committee of Southeast University School of Medicine. The afterload stress mouse model was established as reported ( 23 ). In short, mice were anesthetized with isoflurane (3% isoflurane for induction, 2% isoflurane for maintenance).…”
Section: Methodsmentioning
confidence: 99%